2014
DOI: 10.1177/0269881114523862
|View full text |Cite
|
Sign up to set email alerts
|

Examining relations between alpha power as well as anterior cingulate cortex-localized theta activity and response to single or dual antidepressant pharmacotherapies

Abstract: Electrocortical indices may be useful in predicting antidepressant response. Greater pretreatment alpha power and high rostral anterior cingulate cortex (rACC) theta activity tend to index a favorable outcome. The predictive utility of alpha power asymmetry has been under-explored. Baseline alpha2 (10.5-13.0 Hz) power/asymmetry, rACC theta2 (6.0-8.0 Hz) activity and early (one week) changes in these measures were assessed in relation to antidepressant response by week 12 to three treatment regimens (escitalopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…On the other hand, increased MSE at coarse temporal scales appears to reflect the positive association between treatment response and SPD at lower frequencies (alpha/theta band). Elevated alpha power/amplitude at baseline has been quite consistently observed in eventual responders (vs. non-responders) to various antidepressant pharmacotherapies ( Knott et al, 1996 , Tenke et al, 2011 , Jaworska et al, 2014 ). One interpretation is that this may reflect a hypo-aroused state that benefits from the arousing electrocortical effects of some antidepressants.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, increased MSE at coarse temporal scales appears to reflect the positive association between treatment response and SPD at lower frequencies (alpha/theta band). Elevated alpha power/amplitude at baseline has been quite consistently observed in eventual responders (vs. non-responders) to various antidepressant pharmacotherapies ( Knott et al, 1996 , Tenke et al, 2011 , Jaworska et al, 2014 ). One interpretation is that this may reflect a hypo-aroused state that benefits from the arousing electrocortical effects of some antidepressants.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 51 adults (18–60 years) with a primary diagnosis of MDD, and enrolled in a clinical trial assessing antidepressant pharmacotherapies [details below; (48)], participated in this EEG study. As previously outlined (49), psychiatrists ascertained the diagnosis with the Structured Clinical Interview for DSM (Diagnostic & Statistical Manual of Mental Disorders) IV-TR Diagnoses, Axis I, Patient Version [SCID-I/P; (50)]. Symptom severity was evaluated using the MADRS (46), with scores ≥22 at enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…As described elsewhere (49), prior to each EEG session, participants abstained for >3 h from caffeine and/or nicotine, as well as from alcohol/drugs (excluding prescribed drugs) as of midnight. Using an average scalp reference, AF z ground, and a sampling rate of 500 Hz, EEG recordings were obtained from 32 sites using the 10–20 system (see Supplementary Figure 1) by way of Ag/AgCl electrodes embedded in a cap (EasyCap, Inning A. Ammersee, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Three studies by Jaworska et al [14][15][16] have used EEG measures to predict treatment response in depressed patients randomized to receive escitalopram, bupropion, or their combination (n=51-53). In the first study, the loudness dependence of auditory evoked potentials (LDAEP) was assessed at baseline [14].…”
Section: Pretreatment Predictorsmentioning
confidence: 99%
“…In both these studies, general predictors of outcome were identified which were not specific to the medication received despite the differences in neurochemical actions between escitalopram (an SSRI) and buproprion (a noradrenaline and dopamine reuptake inhibitor). The third study assessed resting frontal and posterior alpha 2 power and asymmetry as well as ACC localized theta [16]. Treatment response (across arms) was weakly predicted by frontal baseline alpha 2 power, with treatment responders exhibiting greater baseline alpha 2 .…”
Section: Pretreatment Predictorsmentioning
confidence: 99%